Emotioncy: A Potential Measure of Readability - Reza PISHGHADAM; Hannaneh ABBASNEJAD (International Electronic Journal of Elementary Education, 2016)
Given the deficiencies of readability formulae as reliable tools for measuring text readability in educational settings, this study aims to offer a new measure to improve the current methods of testing the readability levels of texts through the incorporation of the newly-developed concept of emotioncy. To this end, a group of 221 students were selected from the 2nd to 4th grades of an elementary school. They were given a passage from a 5th grade textbook whose readability was measured by Flesch and Fog indices. The students were asked to fill out an 8-item emotioncy scale along with a difficulty-finding item. One-way ANOVA and correlational analysis were used to analyze the data. Findings indicated that learners’ comprehension increases as a result of an increase in their emotioncy levels. In the end, the results were discussed and some suggestions were made to employ emotioncy in measuring readability.